COMPARISON OF THE INCIDENCE OF ACUTE WATERY DIARRHEA IN CHILDREN AGED 0-12 YEARS WITH EXCLUSIVE BREASTFEEDING AND INFANT FORMULA MILK - Adrianus Andri (Jurnal Medika Hutama, 2023)
Background: This study aimed to compare the incidence of acute watery diarrhea in children aged 0-12 years between exclusive breastfeeding compared to formula milk and diarrhea incidence in Borong Regional Public Hospital, Indonesia. Method: This was a cross-sectional design study with a sample size of 60 infants. Information was obtained through interviews and medical record when admission. Univariate data were presented in distribution frequency table form and bivariate analysis data were analyzed by using Mann-Whitney test. Results: The incidence of diarrhea in children aged 0-12 years was dominated by children who consumed formula milk (68.3%) from the total study sample. The results also found that there was a nonsignificant difference between exclusive breastfeeding compared to infant formula milk and the incidence of diarrhea in infants under 1 year of age. Conclusion: The incidence of diarrhea was lower among infants with exclusive breastfeeding compared to infants with formula milk, although the difference is insignificant.